Curative effect of laparoscopic ureteral end-to-side anastomosis at the pelvic level for a duplex kidney in children - Bian, Zedong; Xiong, Geng; Liu, Tong; Zhi, Yong; Liu, Ming (Frontiers in Pediatrics, 2025)
BackgroundTo analyze the clinical efficacy and experience with laparoscopic ureteral end-to-side anastomosis at the pelvic level for a duplex kidney (DK) in children.MethodsThis was a retrospective analysis of 20 children diagnosed with a complete DK in the pediatric surgery department of the Affiliated Hospital of Southwest Medical University between January 2018 and July 2024. The cohort comprised 15 girls and five boys aged 5–100 months (mean ± SD, 38.5 ± 29.9). There were 16 cases on the left side and four cases on the right side. There were five cases of simple upper ureterovesical junction stenosis, seven cases of upper ureteroceles, seven cases of upper ureteral ectopic opening, and one case of postoperative vesicoureteral reflux with fenestration for upper ureteroceles. The major clinical symptoms were intermittent perineal urinary leakage and repeated infection of the urinary tract. Laparoscopic duplex ureteral end-to-side anastomosis (between the end section of the upper ureter and the lateral section of the lower ureter) at the pelvic level was performed in all patients with an intraoperative indwelling ureteral stent.ResultsLaparoscopy with no conversion to open was undertaken in the 20 cases. The duration of the procedure was 85–140 (112.9 ± 14.3) min. Intraoperative blood loss was 5–15 (8.2 ± 4.4) ml. Postoperative duration of hospital stay was 5–9 (6.5 ± 0.9) days. No anastomosis fistula, anastomotic stenosis, ureteral stump infection or other complications occurred. The ureteral stent was removed 8 weeks after surgery. All children were followed up for 4–68 (median, 32) months. Clinical symptoms disappeared, and the degree of upper renal hydronephrosis decreased.ConclusionsLaparoscopic ureteral end-to-side anastomosis at the pelvic level for a DK in children is safe and efficacious. It is a minimally invasive procedure that is simple with few complications, and merits wider popularization.